Influence of corona discharge on paraffin combustion - Nedybaliuk, O.A.; Fedirchyk, I.I.; Chernyak, V.Ya. (Вопросы атомной науки и техники, 2018)
This article presents the results of investigation on the corona discharge and its influence on the water surface during electrolysis and paraffin combustion. The dependences of the voltage-current characteristics of the discharge from the distance between tungsten needle and grounded metal plate are presented. Emission spectra of flame radiation during the paraffin combustion with the working corona discharge were investigated. The temperature of the paraffin flame was determined from the continuous radiation spectrum.